Harnessing Enzymes for Optimal Poultry Feed Formulations (Mini Review) - Sijid, St. Aisyah; Hafsan, Hafsan; Khudaer, Faten (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
This paper focuses on the use of enzymes in effective and efficient poultry feed formulations. The introduction highlights the importance of good nutrition for poultry and the increasing need for innovative feed formulations due to limited availability and rising prices of feed ingredients. Enzymes are introduced as protein compounds that enhance nutrient digestion and absorption in poultry, potentially reducing feed production costs. However, their widespread use in Indonesia is still limited due to a lack of knowledge. The paper discusses the role of enzymes in poultry nutrition, including their involvement in digestion and nutrient absorption. It also emphasizes the essential nutrients required for poultry growth and development and the factors influencing their nutritional needs. The types of enzymes commonly used in poultry feed formulations, such as phytase, amylase, protease, and lipase, are explored along with their mechanisms of action. Research findings demonstrate the effectiveness and efficiency of using enzymes in improving nutrient availability and feed efficiency, ultimately enhancing poultry production productivity and sustainability. The paper concludes with recommendations for the development and application of enzymes in poultry feed formulations, highlighting the need for careful enzyme selection, dosage adjustment, and consideration of environmental conditions. Furthermore, the importance of integrating enzymes with other feed ingredients and adopting a comprehensive nutrition strategy is emphasized. Overall, the use of enzymes in poultry feed formulations offers significant advantages for modern poultry farming, but careful implementation and further research are necessary to optimize their effectiveness and efficiency.